2006
DOI: 10.1242/jcs.02947
|View full text |Cite
|
Sign up to set email alerts
|

A complex interaction pattern of CIS and SOCS2 with the leptin receptor

Abstract: Hypothalamic leptin receptor signalling plays a central role in weight regulation by controlling fat storage and energy expenditure. In addition, leptin also has direct effects on peripheral cell types involved in regulation of diverse body functions including immune response, bone formation and reproduction. Previous studies have demonstrated the important role of SOCS3 (suppressor of cytokine signalling 3) in leptin physiology. Here, we show that CIS (cytokine-inducible SH2 protein) and SOCS2 can also intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…MfeI-XbaI digest of the first PCR fragment was ligated into an EcoRIXbaI opened pMG1-SVT vector (Eyckerman et al, 2001) with EcoRI site cloned C-terminal of the FLAG tag using site-directed mutagenesis with primers 59-GATGACGACGATAAGGAATTCTCGACCGTGGTAC-39 and 59-GTACCAC-GGTCGAGAATTCCTTATCGTCGTCATC-39. SacII-XbaI digest of the second PCR fragment was ligated into a SacII-XbaI opened pMET7-Etag-Cis vector (Lavens et al, 2006). Human RNF41 was cloned from the pMET7-Etag-hRNF41 vector into a pGEX-4T-2 vector using NotI-XbaI, downstream of glutathione Stransferase, generating the GST-RNF41 vector.…”
Section: Constructsmentioning
confidence: 99%
“…MfeI-XbaI digest of the first PCR fragment was ligated into an EcoRIXbaI opened pMG1-SVT vector (Eyckerman et al, 2001) with EcoRI site cloned C-terminal of the FLAG tag using site-directed mutagenesis with primers 59-GATGACGACGATAAGGAATTCTCGACCGTGGTAC-39 and 59-GTACCAC-GGTCGAGAATTCCTTATCGTCGTCATC-39. SacII-XbaI digest of the second PCR fragment was ligated into a SacII-XbaI opened pMET7-Etag-Cis vector (Lavens et al, 2006). Human RNF41 was cloned from the pMET7-Etag-hRNF41 vector into a pGEX-4T-2 vector using NotI-XbaI, downstream of glutathione Stransferase, generating the GST-RNF41 vector.…”
Section: Constructsmentioning
confidence: 99%
“…As examples of known interaction partners of CIS and SOCS2, we used the intracellular receptor tyrosine motifs Tyr 402 of the EpoR (42) (47,48,52), is possible using the full-length LR. HEK293-T cells were cotransfected with the aforementioned baits and prey constructs encoding the different CIS and SOCS2 variants, combined with the STAT3-responsive rPAPI luciferase reporter.…”
Section: Cis Activity Depends On Elongin B/c Binding-to Investi-mentioning
confidence: 99%
“…Remarkably, although SOCS2 does not bind the Tyr-985 motif, it can interfere with the binding of CIS to this site. This unexpected finding could be explained by the direct binding of SOCS2 on the CIS SOCS box, thereby targeting it for proteasomal degradation [6,10]. More detailed analysis using CIS mutants revealed that CIS binding to the LR and EpoR not only depends on its SH2 domain but also on its SOCS box, with a critical role for the CIS Tyr-253 and the Elongin B/C recruitment site.…”
Section: Lrmentioning
confidence: 99%
“…This way, protein interactions can be studied with the LR in its normal oligomeric configuration [6]. In another MAPPIT setup, we can use the wild-type EpoR ( Figure 1D) [7].…”
Section: Mappit (Mammalian Protein-protein Interaction Trap)mentioning
confidence: 99%
See 1 more Smart Citation